A League Table of Child Poverty in Rich Nations - UNICEF Innocenti Research Centre (United Nations, 2000)
This publication provides the most comprehensive estimates so far of child poverty across the 23 member countries of the Organization for Economic Cooperation and Development (OECD), the world’s wealthiest nations. It highlights the fact that despite a doubling of national incomes in most OECD nations since 1950, a significant percentage of their children are still living in families so materially poor that normal health and growth are at risk. By comparing data from different countries, the publication asks what can be learned about the causes of child poverty and examines the policies that have contributed to the success of lower rates in some countries. In particular, it seeks to explain the situation by exploring the impact on poverty rates of single parenthood, unemployment, low wages and levels of social expenditures. This publication is the first in a series of Innocenti Report Cards on the situation of children in industrialized countries.